Influence of vintage, geographical location and agricultural management on yeast populations in Galician grape musts (NW Spain) - Pilar Blanco; David Castrillo (OENO One, 2022)
The influence of vintage, geographical location and farming system on yeast populations was evaluated in grape musts from Galicia (NW Spain) in three consecutive years. Grape samples were taken in organic and conventional vineyards from four Denominations of Origin (DOs) during the 2013, 2014 and 2015 vintages. Cultivable yeast populations were characterised at the quantitative and qualitative level. The general results show the existence of significant differences for yeast counts in musts among vintages and DOs, but not between farming systems. Given the geographical location of the grapes, the influence of vintage was significant in all DOs; however, the farming system only had a significant impact on viable yeasts in Rías Baixas, although the number of yeasts tended to be higher in organic samples than in conventional ones in most cases. Species richness was location dependent, with Rías Baixas and Ribeira Sacra showing the highest values. In addition, the type of yeasts varied between Denominations of Origin. From a total of 39 different yeast species identified, Metschnikowia spp., Hanseniaspora uvarum and Aureobasidium spp. were the prevailing species. These major yeasts were found to be widely distributed. However, species such as Issatchenkia terricola, Starmerella bacillaris and different species of Candida, Pichia and Zygosaccharomyces genera were mainly found in Rías Baixas and Ribeira Sacra DOs. In contrast, Lachancea thermotolerans was isolated in Monterrei and Ribeiro DOs only. Accordingly, the ANOSIM and PERMANOVA analyses evidenced significant differences in species richness among different DOs and, to a lesser extent, among vintages, but not between farming systems.